Bimekizumab Efficacy and Safety in Japanese Patients with Plaque Psoriasis in BE VIVID: A Phase 3, Ustekinumab and Placebo-Controlled Study - Akihiko Asahina; Yukari Okubo; Akimichi Morita; Yayoi Tada; Atsuyuki Igarashi; Richard G. Langley; Delphine Deherder; Mizuho Matano; Veerle Vanvoorden; Maggie Wang; Mamitaro Ohtsuki; Hidemi Nakagawa (Adis, Springer Healthcare, 2023)
Abstract Introduction Bimekizumab treatment resulted in improved clinical outcomes in patients with moderate-to-severe plaque psoriasis in BE VIVID, a 52-week, phase 3, randomized, ustekinumab and placebo-controlled study. We present data from the BE VIVID Japan patient subpopulation. Methods Globally, patients were randomized to receive bimekizumab 320 mg every 4 weeks (Q4W), ustekinumab (45/90 mg weight-based at baseline and week 4, then every 12 weeks), or placebo (Q4W through week 16, then bimekizumab 320 mg Q4W). Efficacy endpoints included week 16 Psoriasis Area and Severity Index (PASI) 90 and Investigator's Global Assessment (IGA) 0/1, and other outcomes [PASI 100, PASI 75, IGA 0, Dermatology Life Quality Index (DLQI) 0/1, absolute PASI, scalp IGA, Psoriasis Symptoms and Impacts Measure (P-SIM) responses]. Safety analyses were conducted. Results There were 108 Japanese randomized patients (bimekizumab: 62; ustekinumab: 29; placebo: 17). At week 16, bimekizumab-treated patients had a higher clinical response versus ustekinumab and placebo (PASI 90: 85.5% versus 51.7% and 5.9%; IGA 0/1: 82.3% versus 48.3% and 0.0%). Over 52 weeks, improved clinical response was maintained with bimekizumab, including patients switching from placebo at week 16. Overall, the safety profile in Japanese patients was consistent with that observed in the global population. Conclusion Bimekizumab resulted in improved clinical response versus ustekinumab and placebo, and was well-tolerated in Japanese patients. Trial registration NCT03370133. Graphical Abstract